Implementasi Kitab Taisirul Khollaq Dalam Membentuk Akhlak Santri Pondok Pesantren Hidayatul Mubtadiin Sidoharjo Kecamatan Jati Agung - Jujun Juanda; Etika Pujianti; Alfi Zahrotul Hamidah (Journal on Education, 2024)
The book Taisȋrul Kholl aq Fȋ ‘Ilmil Akhlaq is a concise book of the science and morals sections. In this book, it is easy for someone to carry out morals and understand various morals. So that they know for sure the morals that must be carried out and the morals that must be abandoned. Therefore, the author conducted a study on the implementation of learning the book Taisȋrul Kholl aq Fȋ ‘Ilmil Akhlaq at the Hidayatul Mubtadiin Islamic Boarding School. In this thesis, there are three things discussed, namely: (1) How is the learning of the book Taisȋrul Kholl aq Fȋ ‘Ilmil Akhlaq at the Hidayatul Mubtadiin Islamic Boarding School? (2) How is the formation of morals through learning the book Taisȋrul Kholl aq Fȋ ‘Ilmil Akhlaq at the Hidayatul Mubtadiin Islamic Boarding School? (3) What are the factors that influence the formation of students' morals at the Hidayatul Mubtadiin Islamic Boarding School. This type of research uses a qualitative-phenomenological approach. To collect data using observation, interviews, and documentation. Furthermore, the results of these techniques are selected according to the focus of the research. To see the validity of the data, data triangulation techniques are used and then continued with drawing conclusions. After conducting a comprehensive study on the implementation of learning the book Taisȋrul Kholl aq Fȋ 'Ilmil Akhlaq at the Hidayatul Mubtadiin Islamic Boarding School, it can be concluded that: first, learning the book Taisȋrul Kholl aq Fȋ 'Ilmil Akhlaq is running well and effectively as seen from the implementation of effective learning indicators. Second, the formation of morals through learning activities of the Taisȋrul Kholl aq Fȋ ‘Ilmil Akhlaq book at the Hidayatul Mubtadiin Islamic Boarding School includes: the role of teachers of the Taisȋrul Kholl aq Fȋ ‘Ilmil Akhlaq book in forming students' morals has played an active role, the methods used in forming students' morals are the method of examples, role models, giving advice, habituation, and punishment. Third, the factors that influence the formation of morals are the existence of driving factors and inhibiting factors. The driving factors in forming morals in students are the role models of teachers, parents of students.